Analisis Daya Tarik Wisatawan terhadap Museum Sri Baduga Kota Bandung - Riyani Putri Solehah; Alya Indah Ramadhani (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Museum Sri Baduga, located in Bandung, is one of the main cultural institutions that houses important collections related to the history and culture of Sunda. This study aims to explore the attractions of Museum Sri Baduga as a tourist destination, particularly within the context of the rapidly developing local tourism industry. As a popular tourist destination, Bandung offers a variety of options, making it essential to understand the museum's position in attracting visitors and identifying aspects that can be improved. Additionally, this research highlights the museum's role in cultural preservation, positioning it not only as a recreational site but also as an educational center that contributes to the preservation of local heritage amidst globalization. The study seeks to uncover the key factors influencing the appeal of Museum Sri Baduga and how the museum can adapt to changing tourist preferences in the modern era. The findings are expected to provide practical recommendations for museum management in designing more effective marketing strategies to attract visitors from diverse backgrounds, both domestic and international. By focusing on tourist attractions and contributions to cultural preservation, this research aims to offer new insights relevant to the development of Museum Sri Baduga and the tourism sector in Bandung.